SLAH1, a homologue of the slow type anion channel SLAC1, modulates shoot Cl(−) accumulation and salt tolerance in Arabidopsis thaliana - Qiu, Jiaen (Oxford University Press, 2016)

(untitled) (J Exp Bot)
Salinity tolerance is correlated with shoot chloride (Cl(–)) exclusion in multiple crops, but the molecular mechanisms of long-distance Cl(–) transport are poorly defined. Here, we characterize the in planta role of AtSLAH1 (a homologue of the slow type anion channel-associated 1 (SLAC1)). This protein, localized to the plasma membrane of root stelar cells, has its expression reduced by salt or ABA, which are key predictions for a protein involved with loading Cl(–) into the root xylem. Artificial microRNA knockdown mutants of AtSLAH1 had significantly reduced shoot Cl(−) accumulation when grown under low Cl(–), whereas shoot Cl(–) increased and the shoot nitrate/chloride ratio decreased following AtSLAH1 constitutive or stelar-specific overexpression when grown in high Cl(–). In both sets of overexpression lines a significant reduction in shoot biomass over the null segregants was observed under high Cl(–) supply, but not low Cl(–) supply. Further in planta data showed AtSLAH3 overexpression increased the shoot nitrate/chloride ratio, consistent with AtSLAH3 favouring nitrate transport. Heterologous expression of AtSLAH1 in Xenopus laevis oocytes led to no detectible transport, suggesting the need for post-translational modifications for AtSLAH1 to be active. Our in planta data are consistent with AtSLAH1 having a role in controlling root-to-shoot Cl(–) transport.